Remunerasi Berbasis Kinerja: Upaya Meningkatkan Motivasi dan Produktivitas Dosen - Rohida, Leni (Madani: Jurnal Ilmiah Multidisiplin, 2025)
In higher education institutions, performance-based compensation has become a strategic concern in human resource management, especially for private universities (PTS), which face challenges in improving academic quality, worldwide competition, and resource constraints. The purpose of this research is to examine the effects of performance-based compensation schemes on the academic output and motivation of lecturers in private higher education institutions. Using a case study design, this study takes a qualitative approach in a number of Indonesian private universities. To find patterns, themes, and meanings behind lecturers' experiences with the compensation system, data were gathered through in-depth interviews, observations, and document analysis. The data was then subjected to thematic analysis. The results show that lecturers' intrinsic and extrinsic motivation is increased by performance-based compensation, particularly when it comes to community service, teaching effectiveness, and scientific publications. Its execution is still fraught with difficulties, nevertheless, including ambiguous performance metrics, constrained institutional funding, and organizational culture. Prior research has primarily examined the efficacy of compensation in public sectors, with less focus on its precise effects on academic motivation and production at private universities. This study advances the notion of performance management by highlighting the significance of sustainability, equity, and transparency in compensation practices. In practice, the findings help managers in higher education create more equitable, responsible, and performance-based compensation schemes. The report also emphasizes that compensation is a strategic tool to promote a competitive, effective, and quality-focused academic culture rather than just a financial tool.